Current trends on resveratrol bioactivities to treat periodontitis. (August 2021) - Sharifi-Rad, Javad; Quispe, Cristina; Alfred, Mary Angelia; Anil Kumar, Nanjangud Venaktesh; Lombardi, Niccolò; Cinquanta, Lucrezia; Iriti, Marcello; Varoni, Elena M.; Gupta, Gaurav; Chellappan, Dinesh Kumar; Dua, Kamal; Cardoso, Susana M.; et al.
Abstract: Periodontitis is an inflammatory condition causing a severe infection in the gum, leading to tooth loss and related serious health hazards. Severe periodontitis is the sixth most prevalent medical condition, globally affecting about 743 million individuals. Resveratrol (3, 5, 4′-trihydroxystilbene) is a plant polyphenol, extensively popularized during the last decades owing to its promising beneficial effects on human health. A plethora of studies have been carried out and reviewed, retrieved from popular search engines to elucidate the complex bioactivity and the possible health benefits of resveratrol on periodontitis via numerous in vitro and in vivo studies. The underlying mode of action by which resveratrol exerts its health-promoting effects is still to be fully understood and, so far, they are ascribed to a multi-target action. Bioavailability, pharmacodynamics, pharmacokinetics, drug-drug interactions and possible toxicological considerations of resveratrol are also addressed. Resveratrol is indicated as a safe and an effective natural compound against periodontitis and can thus be an interesting alternative to treat this oral disease. Its antimicrobial activity is related to strong antioxidant and anti-inflammatory effects. More in-depth comprehensive studies are needed on human samples to elucidate the structure-activity relationship with bioactivity, for its successful implementation as a useful mainstream drug against periodontitis.